Herbicide Residues in Manure, Compost, or Hay - Jason A. Ferrell; Peter Dittmar; Brent A. Sellers; Pratap Devkota (EDIS, 2020)
Some manure-based products can contain herbicide residues that can affect the growth of sensitive plants. A simple plant bioassay can be conducted to test for herbicide contamination. Written by J. A. Ferrell, P. J. Dittmar, B. A. Sellers, and P. Devkota, and published by the UF/IFAS Agronomy Department, revised May 2020.